Behind the Appearance of Reference Services at the Library University - Rahmi, Lailatur; Susetyo, Tamara A; Irawati, Indiria (Record and Library Journal, 2016)
This study aims to describe the development of reference services at the Library of Universitas Indonesia. The research discussed about innovation in the development of new activities in the reference services. Analyzing reference services from librariansâ point of view concerning the new activities in reference services, including attitudes and policies toward activities. This research takes a descriptive qualitative approach and uses semiotic analysis refering to Semiology of Roland Bathes concerning significance from two stage,Â  denotation and connotation, for analyzing the result of interviews. The results showed that the Universitas Indonesia Library reference service provides some new activities. Librarians become more active, revealed to be closerÂ  to users, and transformation of information technology is seen as one of the competitive need to accompany the development of knowledge. Transfer media eventually have implications not on technology but rather to communication of reference services in the Universitas Indonesia Library.Â